Self-Reported Psychosexual Lifestyles of University Students in Southwestern Nigeria: Implication for Professional Counselling Practice (Global Journal of Human-Social Science, 2013)
Human sexuality is generally described as the sum total of manner through which people experience and articulate their sexual sensation Consequent upon the fact that interest in sexual engagement typically increases at puberty considerable research has been conducted on human sexuality among university students However most of these studies have their focus on premarital sexual behaviour knowledge and attitudes towards sex high risk sexual behaviour and contraceptive usage with restricted attention on socio-psychological aspects of sexual behaviours Recent developments in human sexual behaviour make it imperative for us to increase our knowledge base about diverse aspects of human sexuality On this premise this paper investigated twelve psychosexual construct of 608 university students in Nigeria as well as established gender differences in their sexual esteem and depression Descriptive survey design was adopted and Multidimensional Sexuality Questionnaire MSQ was used to gather data One research question and one research hypothesis guided the study Descriptive statistics analysis indicated that the participants reported higher mean scores for psychosexual constructs of sexual esteem satisfaction internal control consciousness assertiveness external control and motivation respectively and lower mean ratings for sexual depression monitoring preoccupation anxiety and fear of sex in that order Further analysis showed that there were no significant differences on sexual esteem and depression of the participants on gender basis It is recommended among others that counsellors should therefore broaden sexual recovery psychotherapeutic intervention programmes that will further enhance greater or lesser self report as the case may be on university students psychosexual lifestyles
Keywords: self-report; psychosexual; university students; counselling nigeria